Extended drain interval performance of SAE 15W40 CI-4 diesel engine oil under plain and inclined terrain operations - Kim Michael Angelo R. Miraflores (Researcher and Lecturer Society, 2026)
Engine oil plays a critical role in ensuring efficient engine operation and prolonging service life by reducing friction, dissipating heat, and protecting components from wear. This study evaluates the performance of SAE 15W40 mineral multigrade diesel engine oil operated beyond the original equipment manufacturer’s recommended drain interval under varying terrain conditions. Four passenger buses powered by Yuchai, Weichai, and Cummins engines were subjected to a 20,000-kilometer road test covering inclined and plain terrain without oil or filter replacement. Oil condition was assessed using standardized ASTM methods for kinematic viscosity and Total Base Number (TBN). Viscosity values at both 40°C and 100°C remained within acceptable limits throughout the extended interval. TBN values remained above 50% of the fresh oil baseline, indicating retention of alkalinity reserve and additive effectiveness. These results demonstrate that SAE 15W40 diesel engine oil can maintain functional integrity up to 20,000 km under mixed terrain conditions.